Microbiological profile and antibiotic susceptibility of body fluids or swabs of acute leukemia patients with sepsis in a tertiary care hospital - Arka Karmakar; Atreyi Chakraborty; Krishnendu Bandyopadhyay; Biswajit Biswas; Sankar Kumar Das; Atanu Roy; Sayan Chatterjee; Mayank K Vidyarthi; Chayanik Ghosh; Pradip K Bej; Jeker Ali; Akashleena Datta (Asian Journal of Medical Sciences, 2025)
Background: Therapeutic approach to children with acute leukemia and sepsis involves identification of the causative organism and institution of appropriate antimicrobial therapy. The pattern of local flora and antibiotic susceptibility should guide empirical antimicrobial therapy. Aims and Objectives: To identify the bacteria and fungi causing sepsis in children with acute leukemia and study their antimicrobial profile. Materials and Methods: This descriptive observational study with a cross-sectional study design involved 100 consecutive children admitted to the inpatient department with acute leukemia and clinical sepsis with an acute rise of pediatric sequential organ failure assessment score of more than 2. All possible samples, including blood, urine, and pus were sent for culture and sensitivity. Data were analyzed using the Statistical Package for the Social Sciences 23 software. Results: All children had fever. Most common form of infection was pneumonia (27%). Positive microbial growth was found in 23.18% of all the samples (n=220). Gram-negative bacteria were most commonly (49.01%) isolated followed by Gram-positive (27.45%) organisms and fungi (23.52%). Overall, the most common organism was Klebsiella (15.68%). Klebsiella showed 50% sensitivity toward tigecycline and colistin and 37.5% sensitivity toward meropenem, amikacin, and levofloxacin each. Gram-positive organisms showed 100% sensitivity toward vancomycin, linezolid, daptomycin, and tigecycline. We got 23.52% pan resistant organisms. Conclusion: Sepsis is the leading cause of morbidity and mortality among children with acute leukemia. The major causative agents were Gram-negative rods followed by Gram-positive microbes and fungi. Appropriate antimicrobial therapy must be initiated as per the culture sensitivity pattern of the local area to improve outcome and to reduce emergence of drug resistance.